2020
DOI: 10.21203/rs.2.23021/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Genotoxin Colibactin Shapes Gut Microbiota in Mice

Abstract: KEYWORDScolibactin, gut microbiota dysbiosis, microbiome, enterobacteria 62 74 45 25 ; eric.oswald@inserm.fr, https://orcid.org/0000-0002-3017-0081 Tel: + 33 5 67 69 04 15. $ equal contributionAvailability of data and materials. All data are available in the main text or the supplementary materials and via the following repositories: Sequence Read Archive (SRA) database https://submit.ncbi.nlm.nih.gov/subs/sra/ with the assigned identifier PRJNA593936. Ethics approval and consent to participateNot applicable. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…In this study, we found that E. coli production of colibactin is responsible for the growth antagonism toward S. aureus, resulting in significant inhibition of S. aureus in vitro and in vivo during polymicrobial wound infection. E. coli pks genes are upregulated during co-culture with S. aureus, supporting the proposed role of E. coli colibactin as an effector for niche adaptation or domination (Tronnet, Floch et al 2020). Finally, we found that the E. coli two component signal transduction system BarA-UvrY senses the polymicrobial environment leading to the upregulation of the pks island via the CsrA system.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, we found that E. coli production of colibactin is responsible for the growth antagonism toward S. aureus, resulting in significant inhibition of S. aureus in vitro and in vivo during polymicrobial wound infection. E. coli pks genes are upregulated during co-culture with S. aureus, supporting the proposed role of E. coli colibactin as an effector for niche adaptation or domination (Tronnet, Floch et al 2020). Finally, we found that the E. coli two component signal transduction system BarA-UvrY senses the polymicrobial environment leading to the upregulation of the pks island via the CsrA system.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have indicated that colibactin production may cause broad shifts in gut microbial community composition in mice and inhibit the growth of a subset of Staphylococci. 22,23 However, exposure to colibactin did not affect the growth of the vast majority (97%) of bacterial species tested in this prior study, and there is no mechanistic understanding of these reported activities.…”
Section: Introductionmentioning
confidence: 73%
“…The broad-spectrum activity of colibactin in inducing prophages across phylogenetically distinct bacteria is especially striking and suggests this natural product could have effects on many members of a community, potentially accounting for colibactin-associated changes in gut microbiome composition previously observed in animal models. 22 Furthermore, because the virulence behaviors of certain pathogenic bacteria depend on their lysogenic state, it is interesting to consider how colibactin might operate in these situations either positively, by helping to eliminate the pathogen, or negatively, by activating the expression of prophage-controlled virulence factors the pathogen harbors. Such is the case in Shiga toxin (Stx) producing E. coli, where the use of quinolone antibiotics is specifically contraindicated because it increases the induction of the SOS-responsive Stx prophage, which carries the Stx toxin.…”
Section: Discussionmentioning
confidence: 99%
“…100 Furthermore, colibactin can shape gut microbiota composition/function, highlighting how microbes can compete for gut niche utilization. 101 Interestingly, the carcinogenic effects of colibactin-producing E coli are reversed by tumor necrosis factor blockade. 102 F nucleatum and Peptostreptococcus anaerobius are 2 anaerobic pathogens linked to CRC development.…”
Section: Microbial Involvement In Colorectal Carcinogenesis: Mechanistic Insightsmentioning
confidence: 99%